Implementation of the Character of Social Tolerance in Junior High School Students through Video-Based Social Studies Learning - Yetti Hidayatillah; Ali Armadi (Universitas Muhammadiyah Enrekang, 2023)
The aims of this study were 1) to find out the strengthening of social tolerance formed by schools through video-based Civics learning. 2) To determine the strategy for implementing video-based IPS learning at SMP Negeri 2 Sumenep. This study uses a qualitative research approach with data collection techniques using interviews, observation, and documentation. The results of this study state that students at SMP Sumenep still need to strengthen their character of social tolerance. Strengthening the nature of social tolerance is carried out by schools by making student reference books and student journals to build tolerance, especially in instilling values such as democracy, patience, and respect for differences. In this case, The teacher's role is to strengthen the character of tolerance through social studies learning. IPS learning can be done through guided habituation activities using video-based media.